The Coupling of Boundary Integral and Finite Element Methods for the Navier-Stokes Equations in an Exterior Domain (Journal of Computational Mathematics, 2022)
In this paper, a technique of coupling variational formulation of FEM and BIE (boundary integral equation) is used to deal with stationary Navier-Stokes equations in an unbounded domain. We discuss well-posedness for the coupling variational problem, the regularization method and FEM-BEM approximation. Finally, operator splitting and optimal control techniques are used to treat the difficulty of nonlinearity and constraints in computer implementation.